The Effect of Perioperative Fluid Management on Intraocular Pressure during Gynecologic Laparoscopic Pelvic Surgery - Izakson Alexander; Sindawi Ahmad; Ben Shachar Inbar; Pikkel Joseph (Journal of Ophthalmology)
Purpose. Visual loss is a devastating perioperative complication that can result from elevated intraocular pressure (IOP). The Trendelenburg position during surgery increases IOP. The purpose of this study was to quantify IOP changes in patients undergoing laparoscopic hysterectomy, at different time points and body positions throughout the procedure, and to compare fluctuations of IOP during the perioperative period according to two fluid management protocols. Methods. Thirty women scheduled to undergo elective gynecologic laparoscopic pelvic surgery were randomly allocated to receive a liberal or restrictive fluid management protocol. IOP, mean arterial pressure, heart rate, exhaled tidal volume, end-tidal CO2, and ocular perfusion pressure were assessed prior, during, and postsurgery, at 8 time points altogether. Results. Mean changes in IOP were similar for the two protocols; the peak IOP was at the steep (peak) Trendelenburg position. For each protocol, IOP correlated positively with mean arterial pressure, and mean blood pressure correlated with ocular perfusion pressure. Conclusion. IOP was elevated during laparoscopic pelvic surgery and particularly at the steep Trendelenburg position. No differences were found in any of the parameters examined according to a liberal or restrictive fluid management protocol.